Generation of an alternating current discharge in a gas-liquid flow of a copper sulfate solution - Khafizov, A A; Valiev, R I; Gaisin, Az F; Bagautdinova, L N; Gaysin, F M; Sh Basyrov, R (Journal of physics. Conference series, 2022)
In this work, we studied an alternating current discharge in a copper sulfate solution (3% and 10%) with a distance l=150 mm between copper electrodes located inside a dielectric tube with an electrolyte at atmospheric pressure. On the basis of the obtained electrical characteristics of the discharge, a pattern of discharge generation was presented: electrolysis -breakdown - development of the discharge. Volt-ampere characteristics have a falling character, volt-second characteristics are of a direct exponential type, ampere-second characteristics are of a reciprocal exponential type. Using the fast Fourier transform, the voltage and current spectra were obtained. In the voltage spectrum, it was revealed that the voltage is little subject to fluctuations. It has been established that peaks corresponding to frequencies of 50, 150, 250, 350 Hz, etc. are observed in the current spectrum. It is revealed that the intermediate frequencies present in the current spectrum and constituting an almost continuous spectrum appear as a result of stochastic discharge-breakdown processes.